Female farmers Views to Absorb Future Generation in Farming–A Study of Rural Area of Sikkim in North- Eastern India - Dwivedy, Nidhi; ., AjeyaJha (Journal of Social and Development Sciences, 2012)
The present study has analyzed the existing information about female farmer’s views to absorb future generation in farming in the rural area of Sikkim in North- Eastern India and suggested some points so that the socio-economic condition of the stakeholders can be improvedthus making them understand the dynamics of the existing structures and helping the farming sector make sustainablebyattracting the younger age band.Keeping this in mind, data has been collected from 230 female farmers through interviews using a pre-designed schedule from 24 circles from all the four districts of Sikkim State. Based on their subjective judgments, female farmer’s views to absorb future generation in farminghave been measured and analyzed using the Statistical Package for the Social Science (SPSS). Some descriptive statistics, such as percentage, mean, standard deviation as well as one sample t-test of inferential statistics is used to interpret the data. The findings of the study revealthat significantly no more number of sample female farmers on an average feel satisfied with the income they get from agriculture. Data in the study area also discloses that significantly no more number of sample female farmers would like to absorb their future generation in agriculture.Results pertaining to these findings have been discussed in this paper.